1987
DOI: 10.1161/01.hyp.10.2.226
|View full text |Cite
|
Sign up to set email alerts
|

Progress in the battle against hypertension. Changes in blood pressure levels in the United States from 1960 to 1980.

Abstract: SUMMARY Intensive efforts by practicing physicians and public health workers to identify and treat persons with hypertension have been underway for many years. In this report, changes in blood pressure levels in the United States are assessed based on nationally representative health (and nutrition) examination surveys conducted by the National Center for Health Statistics in 1960Statistics in to 1962Statistics in , 1971Statistics in to 1974Statistics in , and 1976Statistics in to 1980. Analysis of ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

1988
1988
2015
2015

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(10 citation statements)
references
References 27 publications
1
9
0
Order By: Relevance
“…The observed decrease in mean systolic blood pressure and increase in the percentage of persons receiving antihypertensive drug therapy across time are consistent with prior reports from the National Center for Health Statistics (3,7,22). The model-based estimates before imputation also supported the finding of an overall secular decline in systolic blood pressure, although not consistently in all age-race-BMI subgroups.…”
Section: Discussionsupporting
confidence: 88%
“…The observed decrease in mean systolic blood pressure and increase in the percentage of persons receiving antihypertensive drug therapy across time are consistent with prior reports from the National Center for Health Statistics (3,7,22). The model-based estimates before imputation also supported the finding of an overall secular decline in systolic blood pressure, although not consistently in all age-race-BMI subgroups.…”
Section: Discussionsupporting
confidence: 88%
“…This approach serves to decrease the blood pressure levels in the general population by relative modest amounts but in large populations has the potential to substantially reduce stroke morbidity and mortality, and to delay the onset of hypertension. 188 Stamler and colleagues estimated two decades ago that a 5 mmHg reduction of SBP in the adult population would result in a 14 percent overall reduction in mortality due to stroke. 189 As presented in Figures 1 and 2 and Table 1, the reduction in systolic blood pressure is consistent with the decline in stroke mortality, and corresponds to the predicted lower stroke mortality rates.…”
Section: Hypertension As a Factor In The Decline In Stroke Mortalitymentioning
confidence: 99%
“…[1][2][3] No studies have reported trends in incidence in hypertension presumably due to the difficulty in collecting such data. Incidence of hypertension cannot be estimated from ambulatory care surveys because the vast majority of medical care for hypertension relates to prevalent rather than to incident cases.…”
Section: Introductionmentioning
confidence: 99%